Telephone Intervention–Problem Solving (TIPS) for Schizophrenia Spectrum Disorders: Responses of Stable Outpatients Over Nine Months. (3rd July 2018) - Beebe, Lora; Smith, Kathlene D.; Oppizzi, Lauren Michelle
ABSTRACT: Medication adherence and community living problems were assessed by a telephone intervention for stable outpatients with schizophrenia spectrum disorders. A majority were white males who lived with family members. We conducted a descriptive analysis of data gathered during weekly calls to 87 participants receiving weekly TIPS for nine months. Analysis included traditional atheoretical content analysis, Pearson correlations, and Chi squares. The following themes emerged: mood disturbances and related symptoms, psychotic symptoms, coping problems, medication adherence, and substance cravings. The most frequently reported problems were mood disturbances: depression and anxiety. Forty two percent of Caucasians versus 72.1% of African Americans were prescribed intramuscular (IM) antipsychotic delivery (Chi square = 8.24, df 2, p = 0.016). Our findings regarding racial differences in antipsychotic delivery method warrant further investigation.